AI-powered search - Grainger, Trey; Turnbull, Doug 1980-; Irwin, Max (Manning Publications, 2025)
AI-Powered Search teaches you to create a search that understands natural language and improves automatically the more it is used. As you work through dozens of interesting and relevant examples, you'll learn powerful AI-based techniques like semantic search on embeddings, question answering powered by LLMs, real-time personalization, and Retrieval Augmented Generation (RAG).
"In video editions the narrator reads the book while the content, figures, code listings, diagrams, and text appear on the screen. Like an audiobook that you can also watch as a video.". - Online resource; title from title details screen (O'Reilly, viewed April 10, 2025)
Keywords: Web search engines; Artificial intelligence; Natural language processing (Computer science); Moteurs de recherche sur Internet; Intelligence artificielle; Traitement automatique des langues naturelles; artificial intelligence; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet